Self-publishing and pretty teapots - Salie, Shazia (WritingThreeSixty: Journal or Research and Creative Text, 2018)
I cannot write this piece and not credit the atmosphere created, so here is my experience of both The Open Book Festival and the Self-Publishing session held on the 7th September 2017 at the District Six Homecoming Centre (HCC).